Monday Pon Activities in the Formation of Students’ Religious Character in the 21st Century (Case Study at MI Kresna, Mlilir District, Madiun Regency) - Indah Fatmawati; Andy Litehua; Yuli Umro’atin (Proceeding International Conference on Religion, Science and Education, 2023)
The 21st century which influences people’s lifestyles makes parents and teachers must be able to face every challenge that exists, including how to choose and prepare education for their children. It is undeniable that technological developments are also accompanied by negative impacts that occur on students in school. Responding to this phenomenon, MI Kresna, which is located in Mlilir District, Madiun Regency, organizes activities in the form of morning habituation in the form of: tartil, asmaul husna, qira’ah, memorizing jus 30, istigosah and reading ratib. In addition to these activities, there are also activities carried out every Sunday Pon in the form of Islamic boarding school activities attended by Grade 4, 5 and 6 students at MI Kresna. The technique of this activity is that students stay at school and are scheduled alternately per class level to train students to be able to live independently and introduce them to religious values with the hope that later they can continue to the Islamic boarding school level. This study aims to analyze how the application of religious values in the activities carried out by MI Kresna to face challenges in the 21st century. This research is a type of qualitative research by collecting data in the field by observation, interviews and documentation, the elaboration of data is carried out descriptively and the method of analysis data using the theory of habituation. From this research, a common thread can be drawn, by carrying out Monday Pon activities in the form of habituation at MI Kresna, it is hoped that students will be able to grow and develop with strong religious character so that they are able to live adaptively in the ongoing 21st century.